Association Between Blood Lead Level With High Blood Pressure in US (NHANES 1999–2018) - Huang, Ziyao (Frontiers in Public Health, 2022)
Background: Lead is a toxic metal for human’s health, but the effect for blood pressure was still controversial. The object of the study was to demonstrate the association between blood lead level with blood pressure and hypertension. Methods: We used the database from the National Health and Nutrition Examination Survey 1999-2018 to preform a cross-sectional study. We preformed multivariate regressions to examine the association between blood lead level with hypertension and blood pressure, then subgroup analysis were preformed. Results: A total of 32289 participants were included into our study, but no significant difference were found between blood lead level with hypertension. However, the association became positive between blood lead level with systolic and diastolic pressure. In the subgroup analysis stratified by race, the association in non-Hispanic White and Black was still existed. Conclusion:The association between blood lead level with hypertension was not significant, but it were positively associated with blood pressure. And the association in non-Hispanic White and Black were also significant.